Synergies and Post-Acquisition Performance: Differences versus Similarities in Resource Allocations - Harrison, Jeffrey S.; Hitt, Michael A.; Hoskisson, Robert E.; Ireland, R. Duane (Journal of Management, 1991)
Theory suggests that synergy is an essential ingredientfor value creation to occur as a result of acquisitions. This dominant theory often argues for similarities among resources in the acquiring and targetfirms. However; it is argued here that uniquely valuable synergy might be created where differences (versus similarities) exist between resources in the acquiring and target firms. Tests of these competing hypotheses confirmed that differences contributed significantly to performance in the mergedfirm. Thisfinding may suggest that traditional distinctions between related and unrelated mergers may not be as useful as once thought. A focus on specific resources rather than strategy types in the merger and acquisition research may better explain firm performance.